2018
DOI: 10.3389/fimmu.2018.00964
|View full text |Cite
|
Sign up to set email alerts
|

Aire Disruption Influences the Medullary Thymic Epithelial Cell Transcriptome and Interaction With Thymocytes

Abstract: The function of medullary thymic epithelial cells (mTECs) is associated with thymocyte adhesion, which is crucial for the negative selection of autoreactive thymocytes in the thymus. This process represents the root of central tolerance of self-components and prevents the onset of autoimmune diseases. Since thymic epithelia correspond to an important target of donor T cells during the onset of chronic graft-vs-host-disease, mTEC-thymocyte adhesion may have implications for alloimmunity. The Aire and Fezf2 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 61 publications
(94 reference statements)
5
23
0
2
Order By: Relevance
“…31 Aire is also a vital transcriptional regulator in mTECs which plays significant roles in the process of controlling mTECthymocyte adhesion. 32 Consistent with this, our data suggested that CD4+ T cells decreased and CD8+ T cells increased in mice with reduced Aire expression. We demonstrated that RSV supplementation improved the Aire mRNA relative expression greatly.…”
Section: Discussionsupporting
confidence: 89%
“…31 Aire is also a vital transcriptional regulator in mTECs which plays significant roles in the process of controlling mTECthymocyte adhesion. 32 Consistent with this, our data suggested that CD4+ T cells decreased and CD8+ T cells increased in mice with reduced Aire expression. We demonstrated that RSV supplementation improved the Aire mRNA relative expression greatly.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that the expansion of SP thymocytes occurring between D12 and D28 might have led to the increase in mTEC numbers. This is consistent with the fact that the development of the mTEC compartment during embryogenesis requires interaction between TECs and positively selected thymocytes (25)(26)(27)(28)(29)(30)(31), and suggests that a similar crosstalk is instrumental to the maintenance of mTECs in the adult thymus. Representative profiles of cTECs and mTECs at different time points during pregnancy and postpartum regeneration are shown in Supplementary Figure 1.…”
Section: Thymic Epithelium Does Not Suffer Cell Loss During Pregnancysupporting
confidence: 86%
“…At this stage, medullary thymic epithelial cells orchestrate the presentation of antigens from virtually all organs to maturing thymocytes via MHC type II molecules expressed on thymic dendritic cells (19) . This process called promiscuous gene expression is highly regulated by the autoimmune regulator (AIRE), an intra-nuclear regulating factor of gene expression highly active in medullary thymic epithelial cells (20,21) . This process leads to the acquisition of self-tolerance by the negative selection of CD4þCD8þ thymocyte subsets that are potentially autoreactive against self-antigens (22) .…”
mentioning
confidence: 99%